25 years of Scientific and Educational Cooperation between the Department of Natural Sciences at New Bulgarian University and the Space Research and Technology Institute at the Bulgarian Academy of Sciences - Mardirossian, Garo; Berberova, Ralitza (Annual of Natural Sciences Department, 2021)
The paper presents the results of the scientific and educational cooperation in the field of earth sciences and ecology between the Department of Natural Sciences at New Bulgarian University (NBU) and the Space Research and Technology Institute at the Bulgarian Academy of Sciences (SRTI-BAS) for the period 1996-2021.